Novel PORCN mutation in a severe case of Focal Dermal Hypoplasia (2016)
Focal dermal hypoplasia is a rare genetic disease characterized 8-year-old female who sought genetic counseling for multiple malformations, aggressive behavior and intellectual disability. Gene analysis confirmed focal dermal hypoplasia.